The Roles of Two Type VI Secretion Systems in Cronobacter sakazakii ATCC 12868 - Wang, Min; Cao, Hengchun; Wang, Qian; Xu, Tingting; Guo, Xi; Liu, Bin (Frontiers in Microbiology, 2018)
Type VI secretion system (T6SS), which has been found in 25% of gram-negative bacteria, is a crucial virulence factor in several pathogens. Although the T6SS gene loci have been discovered in Cronobacter species, one of the major opportunistic foodborne pathogens, its function has not been determined. In this study, the roles of two phylogenetically distinct T6SS gene clusters in Cronobacter sakazakii ATCC12868 were investigated. Through analysis of 138 genome sequences of C. sakazakii strains, we found that one T6SS gene cluster (T6SS-1) was ubiquitous in all of the examined strains, while another (T6SS-2) was absent or degenerated in a large proportion of the strains (n=97). In addition, we confirmed that T6SS-1 acquired antibacterial function through an in-frame deletion in the vasK and hcp genes. Compared with the wild-type strain, the T6SS-2-deficient mutant presented a much stronger colonization of organs when infecting neonatal rats. Thus, it was proposed that T6SS-2 played a role in pathogenic processes. This is the first study to investigate the functions of T6SS in C. sakazakii, and the results will extend our understanding of the pathogenic and phylogenetic characteristics of C. sakazakii.